Fruit Coating with Chitosan and Beeswax to Increase Papaya Shelf Life - Mukdisari, Yurisqi; Suketi, Ketty; Widodo, Winarso Drajad (Journal of Tropical Crop Science, 2016)
Papaya (Carica papaya) is a climacteric fruit with an increased respiration rate during ripening process. Papaya respiration rate can be inhibited by providing a coating on the surface of the fruits, including chitosan, a polysaccharide derived from shrimp shell waste, or beeswax.The purpose of this research was to examine the effects of chitosan and beeswax coating on the shelf life and quality of papaya Callina fruit during storage. Results of the experiments showed that fruit coating with chitosan and beeswax can extend the shelf life of papaya Callina by four to five days compared to control due to inhibition respiration rate of papaya fruits during storage.The use of chitosan and beeswax was beneficial to maintain the physical and chemical quality of papaya Callina fruits.